Effectiveness of Mangrove Kateng Leaf Extract (Avicennia lanata Ridl.) as a Natural Preservative for Fresh Vannamei Shrimp Meat (Litopenaeus vannamei): Efektivitas Ekstrak Daun Kateng Mangrove (Avicennia lanata Ridl.) sebagai Pengawet Alami Daging Segar Udang Vannamei (Litopenaeus vannamei) - Pramudya, Arkan Setia; Yachya, Arif; Suparman, Suparman (Universitas Muhammadiyah Sidoarjo, 2025)
Vannamei shrimp (Litopenaeus vannamei) is a mainstay export fishery product. Its meat is rich in protein and fat, but the quality is easy to reduce due to decay over storage time. Decay occurs due to bacterial activity and oxidation. The freezing preservation method requires relatively expensive costs, so it often uses hazardous materials for substitution, such as formalin as a preservative. Therefore, it is necessary to research the effectiveness of natural materials sourced from plant organs as relatively safe preservatives. One of the plants is Kateng (Avicennia lanata), whose leaves are rich in secondary metabolite compounds that inhibit growth and kill bacteria. This study aims to determine the effectiveness of A. lanata water extract as a natural preservative for fresh Vannamei shrimp meat. The research was an experimental laboratory study using a completely randomized design with three repetitions. The concentrations of the A. lanata water extract solution tested were 0, 25, 50, 75, and 100% (w/v). Variations in the storing time of shrimp meat after being soaked in the test extract solution were 2 and 4 hours. The storage was at room temperature. The parameters of shrimp meat quality observed at the end of the storage period included total bacterial population, hydrogen sulfide gas (H2S) production, acidity level (pH), and trimethylamine (TMA) content. The results showed that the quality of fresh Vannamei shrimp meat depends on various concentrations of A. lanata water extract solution (0-100% w/v) and storage periods (2 and 4 hours). Water extract of A. lanata leaves at a concentration of 75% (w/v) with 2 hours of storage is the optimal concentration and storage time to preserve fresh L. vannamei shrimp meat naturally.